Determination of the packing fraction in photonic glass using synchrotron radiation nanotomography. (6th October 2016) - Ogurreck, Malte; do Rosario, Jefferson J.; Leib, Elisabeth W.; Laipple, Daniel; Greving, Imke; Marschall, Felix; Last, Arndt; Schneider, Gerold A.; Vossmeyer, Tobias; Weller, Horst; Beckmann, Felix; Müller, Martin
Abstract : Synchrotron radiation nanotomography has been used to quantify the packing fraction in a photonic glass sample. Abstract : Photonic glass is a material class that can be used as photonic broadband reflectors, for example in the infrared regime as thermal barrier coating films. Photonic properties such as the reflectivity depend on the ordering and material packing fraction over the complete film thickness of up to 100 µm. Nanotomography allows acquiring these key parameters throughout the sample volume at the required resolution in a non‐destructive way. By performing a nanotomography measurement at the PETRA III beamline P05 on a photonic glass film, the packing fraction throughout the complete sample thickness was analyzed. The results showed a packing fraction significantly smaller than the expected random close packing giving important information for improving the fabrication and processing methods of photonic glass material in the future.